An observational study on the prevalence of congenital hypothyroidism and factors affecting TSH levels in premature babies at tertiary care rural centre - Kerudi, Madhu P.; Kumar, G. M.; Mahendrappa, K. B. (International Journal of Contemporary Pediatrics, 2023)
Background: Premature babies, particularly those with very low birth weight (VLBW), are at a higher risk of developing congenital hypothyroidism. The inadequate development of the hypothalamic-pituitary axis in preterm infants contributes to the higher prevalence of this condition in this population. However, the optimal screening and treatment protocols for congenital hypothyroidism in preterm newborns remain unclear. Methods: This was a hospital-based observational study conducted over a period of 18 months. The study included 150 preterm babies born at the Sri Adichunchanagiri hospital and research centre. Non-probability sampling was used to select the study subjects. Data on demographic and clinical factors were collected from mothers and newborns. Blood samples were collected at day 3 of life to estimate thyroid-stimulating hormone levels. Correlations between TSH levels and various parameters were analyzed using statistical methods. Results: The study found that the prevalence of congenital hypothyroidism in preterm newborns was 2%. The mean TSH level at day 3 was 7.56 mIU/L, and 9.3% of cases had TSH levels above 20 mIU/l. Significant associations were found between high TSH levels and primiparity, vaginal delivery, and maternal gestational diabetes mellitus. There was an inverse correlation between TSH levels and gestational age, birth weight, and Apgar scores at 1 and 5 minutes. Conclusions: The study revealed a prevalence of congenital hypothyroidism of 2% in preterm newborns. Risk factors such as primiparity, vaginal delivery, and maternal GDM were associated with high TSH levels. These findings highlight the importance of screening and early detection of congenital hypothyroidism in premature babies to improve outcomes.